2010
DOI: 10.1016/j.pain.2010.04.013
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of pregabalin in the treatment of neuropathic pain associated with chronic lumbosacral radiculopathy

Abstract: We evaluated the efficacy of pregabalin in patients with chronic lumbosacral radiculopathy. This randomized, controlled, withdrawal trial included five phases: screening (4-18 days); run-in (4-10 days) to screen out placebo responders; single-blind (28 days) to identify pregabalin responders; double-blind to randomize responders to pregabalin or placebo (35 days); and final study medication taper (7 days). The primary endpoint was time to loss of response (LOR) during the double-blind phase (1-point increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
121
0
14

Year Published

2010
2010
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(139 citation statements)
references
References 31 publications
4
121
0
14
Order By: Relevance
“…Moreover, the possible dominance of one pain type is of therapeutic relevance [33,3], and may account for individual differences in responsiveness to anti-neuropathic agents, such as pregabalin, as documented in recent clinical trials of patients with lumbar and cervical radiculopathies [4,59].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the possible dominance of one pain type is of therapeutic relevance [33,3], and may account for individual differences in responsiveness to anti-neuropathic agents, such as pregabalin, as documented in recent clinical trials of patients with lumbar and cervical radiculopathies [4,59].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that pregabalin was effective in the treatment of neuropathic pain associated with chronic lumbosacral radiculopathy 14) . However, little is known about the therapeutic efficacy of pregabalin for each pathomechanism of the leg symptoms of LSS.…”
Section: Introductionmentioning
confidence: 99%
“…Analgesic pharmacotherapy comprises not only the classical pain-killing drugs (i.e., opioids and non-steroidal anti-inflammatory drugs) but also agents belonging to other pharmacological groups (analgesic adjuvants) used as an add-on therapy in the treatment of intractable pain (Baron et al, 2010;Eisenberg et al, 2007;Finnerup et al, 2005). The available analgesic drug are not fully effective in a significant proportion of patients and some serious side effects frequently accompany the analgesic therapy account for a strong medical demand for the identification of new pain-relieving agents.…”
Section: Introductionmentioning
confidence: 99%